Approche critique du mécanisme de règlement des différends commerciaux devant la CCI - Kesse, Julia Sainte-Colombe (Université de Montréal, 2026)
Cette étude analyse de manière critique le mécanisme de résolution des litiges commerciaux de la Chambre de commerce internationale (CCI) en trois étapes : précontentieux, contentieux et post contentieux. Il examine d’abord l’évolution des méthodes amiables telles que la médiation, la conciliation ou les commissions de règlement des différends mises en œuvre par la CPI pour la prévention des conflits. Ensuite, la validité, les conditions de validité et les conditions applicables de la procédure d'arbitrage sont analysées. Enfin, elle se penche sur la question de la contestation de l'exécution du jugement, notamment par le biais de la Convention de New York. Cet ouvrage met en lumière les apports et les lacunes du système, en insistant sur les différences sectorielles, les résistances culturelles (en Afrique) et les défis de légitimation. L’on a conclu qu’il était nécessaire de renforcer la complémentarité entre le règlement amiable et l’arbitrage afin d’établir une justice commerciale plus efficace, universelle et durable. This thesis critically analyses the International Chamber of Commerce (ICC) mechanism for resolving commercial disputes at three stages: pre-dispute, dispute and post-dispute. First, it examines the development of amicable procedures such as mediation, arbitration or dispute settlement bodies adopted by the ICC to prevent conflicts. It then analyses the effectiveness of arbitration proceedings, the conditions for their entry into force and the elements for their applicability. Finally, it questions the enforcement of arbitration awards, especially under the New York Convention. The study highlights the strengths and weaknesses of the system, underlining sectoral differences, cultural resistance (in Africa and Asia) and legitimacy challenges. It concludes that in order to build a more effective, universal and sustainable commercial justice system, it is necessary to strengthen the complementarity between amicable settlement and arbitration.
Keywords: Alternative; Arbitrage commercial international; Chambre de commerce internationale; Commercial litigation; Contentieux commercial; Convention de New York (1958); Enforcement of arbitral awards; Exécution des sentences arbitrales; International Chamber of Commerce (ICC); International commercial arbitration; International commercial mediation; Médiation commerciale internationale; New York Convention

L’impact des clauses d’arbitrage entre investisseurs étrangers et Etats sur la souveraineté : une analyse de l'équilibre entre protection des investisseurs étrangers et la souveraineté - Ahouyanganga Matondo, Dan Salomon (Université de Montréal, 2026)
Ce mémoire analyse l’impact des clauses d’arbitrage entre investisseurs étrangers et États sur la souveraineté étatique, en s’intéressant à l’équilibre entre protection des investisseurs et capacité réglementaire des États. Dans un contexte de mondialisation marqué par les crises sanitaires et les tensions géopolitiques, les États cherchent à attirer les investissements étrangers tout en préservant leur souveraineté économique. Le travail met en lumière le rôle du mécanisme RDIE, permettant aux investisseurs étrangers de contester les mesures étatiques devant des tribunaux arbitraux internationaux, contournant ainsi les juridictions nationales. Bien qu’il sécurise les flux d’investissements et renforce la confiance des investisseurs, le RDIE peut créer des déséquilibres, limitant la marge de manœuvre des États dans des domaines sensibles tels que la santé publique, l’environnement ou les droits sociaux. À travers l’analyse de cas emblématiques et des traités internationaux d’investissement, le mémoire propose des pistes pour concilier la protection juridique des investisseurs et le respect de la souveraineté étatique. Il conclut que le RDIE, tout en étant un outil essentiel de sécurisation des investissements, nécessite des réformes pour garantir un équilibre durable entre intérêts privés et intérêt général. This research study will analyze the impact of arbitration clauses between foreign investors and states on state sovereignty, focusing on the balance between investor protection and the regulatory capacity of states. In a globalized context marked by health crises and geopolitical tensions, states seek to attract foreign investment while preserving their economic sovereignty. The study highlights the role of the ISDS mechanism, which allows foreign investors to challenge state measures before international arbitration tribunals, thus bypassing national courts. Although it ensures investment flows and strengthens investor confidence, the ISDS system can create imbalances, limiting states' room for maneuver in sensitive areas such as public health, the environment, and social rights. Through analysis of historical cases and international investment treaties, the thesis proposes ways to reconcile legal protection for investors with respect for state sovereignty. It concludes that while ISDS remains an essential tool for securing investments, it requires reform to ensure a sustainable balance between private interests and the public good.
Keywords: Arbitration clauses; Clauses d’arbitrage; Foreign investors; ISDS; Investisseurs étrangers; Investment treaties; RDIE; Souveraineté; Sovereignty; States; Traités d’investissement; États

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

L'autonomie de la clause compromissoire en droit de l'arbitrage Marocain et Québécois: entre consécration et limites - Rafai, Khawla (Université de Montréal, 2024)
Le principe de l’autonomie de la clause compromissoire est au cœur du mécanisme de l’arbitrage, tout en demeurant complexe et polyvalent. Cette étude met en lumière les différentes dimensions de ce principe, tout en identifiant ses limites face aux exigences fondamentales de justice et d’ordre public. L’autonomie de la clause compromissoire signifie d’abord que cette clause, bien qu’intégrée dans un contrat principal, existe et survit de manière indépendante. Concrètement, cela veut dire qu’une contestation ou une invalidité du contrat principal n’affecte pas automatiquement la clause compromissoire. Cette indépendance permet aux parties de préserver leur engagement à soumettre les litiges à un tribunal arbitral, offrant ainsi une sécurité juridique et une continuité au processus de résolution des conflits. L’arbitrage repose ici sur un engagement volontaire et anticipé, qui ne saurait être remis en cause par des circonstances affectant le contrat lui-même. Au-delà de cette indépendance, l’évolution du principe d’autonomie a permis d’introduire une autre dimension : la liberté de choix dans les règles qui régissent la clause compromissoire. Cela signifie que les parties ne sont pas nécessairement liées aux règles du contrat principal. Cette forme d’autonomie favorise la flexibilité, permettant aux parties de concevoir une procédure arbitrale adaptée à leurs besoins spécifiques. Cependant, cette liberté rencontre certaines limites, notamment en matière d’ordre public, qui agit comme un rempart pour protéger les valeurs fondamentales de justice et d’équité. Un autre aspect fondamental de ce principe est son interaction avec le concept de compétence-compétence, selon lequel le tribunal arbitral est habilité à statuer sur sa propre compétence. Cette relation étroite entre les deux principes peut créer une certaine confusion, car si l’autonomie de la clause concerne sa validité et son indépendance, la compétence-compétence relève plutôt du pouvoir décisionnel des arbitres. Toutefois, ces deux notions, bien que distinctes, contribuent ensemble à garantir l’efficacité de l’arbitrage en permettant de résoudre rapidement les questions liées à la compétence et à la validité de la clause. L’étude aborde également la transmissibilité de la clause compromissoire, qui pose un défi théorique à l’idée d’autonomie. En cas de cession ou de transfert du contrat principal, la clause compromissoire accompagne généralement le contrat, ce qui semble paradoxal par rapport à son indépendance. Cette apparente contradiction s’explique toutefois par la nécessité pratique d’assurer la continuité des mécanismes d’arbitrage, en particulier dans des situations complexes comme les contrats multipartites ou les groupes d’entreprises. Enfin, le principe d’autonomie, malgré sa robustesse et son importance dans l’arbitrage, demeure encadré. La protection des intérêts fondamentaux des parties les plus vulnérables et des principes essentiels de justice impose des limites nécessaires. L’ordre public joue ici un rôle clé en veillant à ce que la liberté contractuelle ne se traduise pas par une atteinte aux droits fondamentaux ou aux valeurs essentielles de la société. En conclusion, l’autonomie de la clause compromissoire est un instrument essentiel qui garantit la stabilité et l’efficacité de l’arbitrage. Elle repose sur une double dynamique : une indépendance par rapport au contrat principal et une flexibilité permettant aux parties d’organiser librement la procédure arbitrale. Toutefois, cette autonomie doit coexister avec des limites claires pour concilier la liberté contractuelle avec les exigences de justice, assurant ainsi un équilibre nécessaire entre efficacité et protection des principes fondamentaux. The principle of the autonomy of the arbitration clause is central to the arbitration mechanism, while remaining both complex and multifaceted. This study sheds light on the various dimensions of this principle and identifies its limits in the face of fundamental justice and public policy requirements. The autonomy of the arbitration clause primarily signifies that the clause, although incorporated into a principal contract, exists and survives independently. In practical terms, this means that a dispute regarding or the invalidity of the principal contract does not automatically affect the arbitration clause. This independence enables the parties to uphold their agreement to submit disputes to arbitration, thereby ensuring legal certainty and continuity in conflict resolution processes. Arbitration thus rests on a voluntary and preemptive commitment that cannot be undermined by circumstances affecting the main contract. In addition to this independence, the development of the principle of autonomy has introduced another significant aspect: the freedom of the parties to determine the rules governing the arbitration clause. This autonomy allows the parties to deviate from the rules of the principal contract, fostering flexibility and enabling the design of arbitration procedures that meet their specific needs. However, this freedom is not without limits, particularly where public policy intervenes as a safeguard to preserve fundamental principles of justice and fairness. A crucial component of this principle is its interaction with the kompetenz-kompetenz doctrine, which empowers the arbitral tribunal to rule on its own jurisdiction. This close relationship between the two concepts may cause confusion: the autonomy of the arbitration clause concerns its validity and independence, whereas kompetenz-kompetenz pertains to the decision-making authority of arbitrators. Despite their distinctions, both principles collectively enhance the effectiveness of arbitration by facilitating the prompt resolution of jurisdictional and validity-related challenges. This study also explores the issue of the arbitration clause’s transmissibility, which presents a theoretical challenge to the notion of autonomy. In cases where the principal contract is assigned or transferred, the arbitration clause typically follows the contract, creating a seemingly paradoxical situation regarding its independence. This apparent contradiction can, however, be justified by the practical need to maintain the continuity of arbitration mechanisms, particularly in complex contexts such as multiparty contracts or corporate groups. Ultimately, despite its essential role and resilience, the autonomy of the arbitration clause is subject to necessary constraints. The protection of vulnerable parties and the preservation of fundamental principles of justice impose clear limitations. Public policy serves as a crucial safeguard to ensure that contractual freedom does not infringe upon fundamental rights or societal values. In conclusion, the autonomy of the arbitration clause is a cornerstone of arbitration’s stability and effectiveness. It is characterized by independence from the principal contract and the flexibility afforded to the parties in shaping their arbitration proceedings. However, this autonomy must be balanced against clear limits to harmonize contractual freedom with justice requirements, ensuring an essential equilibrium between efficiency and the protection of core principles.
Keywords: Arbitrability; Arbitrabilité; Arbitration; Arbitration clause; Autonomie; Autonomy; Clause compromissoire; Extension; Ordre public; Public policy; Transmissibility; Transmission

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

L’encadrement juridique de la médiation dans l’espace OHADA : analyse critique de l’acte uniforme relatif à la médiation - Mukuamu, Prince (Université de Sherbrooke, 2023)
Aujourd'hui plus qu'hier, la médiation suscite l’intérêt tant des chercheurs, des praticiens, que des politiques. Cet intérêt se matérialise notamment par les différents cadres juridiques dont elle bénéficie dans plusieurs législations. Afin de promouvoir la médiation au sein de ses États membres, L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a adopté le 23 novembre 2017 un Acte Uniforme relatif à la Médiation (AUM). Après avoir adopté depuis plus de deux décennies un Acte uniforme sur l’arbitrage, l’organisation régionale confirme sa volonté de promouvoir les modes alternatifs de règlement de conflits dans le domaine du droit des affaires. Cependant, l’AUM est un instrument juridique particulier attendu qu'il est le premier de son genre à s’appliquer également aux domaines non encore régis par le droit OHADA. Toutefois, si la médiation tend à se développer de plus en plus, il convient de prendre garde à ce que cette évolution, notamment en ce qui concerne son encadrement légal, ne conduise pas à sa dénaturation. Voilà l’un des défis auquel est également soumis le législateur OHADA.
Keywords: AUM; Acte uniforme; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; OHADA

L'attractivité de l'arbitrage au regard des nouvelles réformes de l'OHADA - Kounouho, Marcson Smile Geoffroy Tagnon (Université d'Abomey-Calavi, 2022)

L'arbitrage à l’épreuve des procédures collectives et de l’intervention du juge en droit de I’OHADA. - Kante, Souleymane (Université Jean Lorougnon Guédé, 2021)
Si l’on définit l’arbitrage simplement comme un mode de règlement des différends administré par les particuliers non investis de leur mission par l’Etat. Il n’en demeure pas moins que ce mode de règlement des différends ne saurait évoluer seul. C’est ainsi que l’ordre public des procédures collectives et l’intervention du juge étatique impact tant l’arbitrage. Il a paru important de jauger leur impact sur l’arbitrage. L’analyse effectuée à travers une méthode exégétique des textes communautaires et internationaux a permis de constater que les procédures collectives et l’intervention du juge étatique sont facteurs de désordre dans l’arbitrage. Toutefois, il convient de relever une certaine survie de l’arbitrage face aux procédures collectives et à l’intervention du juge étatique.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Juge étatique; OHADA; Procédures collectives; Survie

L'arbitrage en droit aérien et spatial - Soliveres, Théo (Aix-Marseille Université, 2021)
Keywords: Arbitrage; Arbitration; Droit aérien; Droit spatial

O recurso à arbitragem no âmbito das sociedades comerciais : os conflitos societários internos - Vaz, Juliana Touro Cerejo Rabaça (Universidade Católica Portuguesa, 2020)
A presente dissertação tem como objetivo analisar, à luz do ordenamento jurídico português, a possibilidade e adequação do recurso ao instituto da arbitragem como meio de resolução dos litígios intrassocietários, isto é, os litígios emergentes das relações entre os sócios de uma sociedade, os resultantes das relações entre os sócios e a própria sociedade, ou ainda no âmbito das relações entre os sócios ou a sociedade per si e os titulares dos órgãos de administração ou de fiscalização da mesma. Para tal, foi inicialmente adotada uma perspetiva comparatística com outros ordenamentos jurídicos. Posteriormente, foi adotada uma abordagem expositiva, do instituto da arbitragem em Portugal, analisando inicialmente de um modo geral, especificando depois o propósito principal da presente dissertação – a arbitrabilidade dos litígios intrasocietários, nomeadamente o regime da convenção de arbitragem, do tribunal arbitral e da própria sentença arbitral. Avaliadas as vantagens e os inconvenientes do recurso à arbitragem enquanto meio de resolução alternativa de litígios, e a sua aplicabilidade aos litígios intrassocietários, tomando como referência a escassa regulamentação deste instituto neste domínio no nosso ordenamento jurídico, conclui-se a presente dissertação com uma proposta de regulamentação legal e outra estatutária da arbitragem dos referidos litígios intrasocietários.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Entreprises commerciales; Litige interne

L'administration de la preuve en arbitrage international au regard des règles de l'International Bar Association ainsi que des règles de Prague - Gommé, Laurence (Université de Liège, 2019)
Ce travail traite principalement de l’administration de la preuve en arbitrage international. Cette question divise les praticiens du monde arbitral en deux camps : ceux issus de la tradition de common law et ceux issus de la tradition de civil law. Dans un premier temps, les règles de l’International Bar Association relatives à l’administration de la preuve ont tenté de concilier ces deux traditions juridiques différentes. Dans un second temps, les règles de Prague ont, récemment, été publiées ce qui nous permettra, dans ce travail, d’analyser les deux systèmes pour ensuite les comparer. Enfin, nous essayerons d’envisager l’avenir de ces nouvelles règles de Prague.
Keywords: Arbitrage; Civil law; Common law; Preuve; Production de documents; Règles de Prague; Règles de l'IBA; Soft law

L'intervention du juge étatique dans le cadre des mesures provisoires ou conservatoires en présence d'une convention d'arbitrage : analyse du droit belge - Sabatini, Fiona (Université de Liège, 2019)
L’arbitrage, en tant que justice privée, s’entend comme un mode de règlement des différends tant alternatif qu’antagoniste de la justice étatique. Dépourvu d’imperium, l’arbitre peut nécessiter le soutien et la coopération du juge pour traiter une procédure arbitrale. Divers droits contemporains de l’arbitrage envisagent explicitement le recours aux mesures provisoires et conservatoires lors d’un arbitrage interne ou international sans nécessairement apporter une définition de ces mesures. En matière d’arbitrage, les mesures provisoires et conservatoires détiennent un rôle capital préalablement ou durant l’instance arbitrale. Elles permettent le maintien d’une preuve, d’une situation de fait ou de droit et garantissent ou préparent une exécution efficiente et rapide de la sentence. La réunion dans le chef de l’arbitre de la compétence au fond et celle au provisoire peut être défavorable aux intérêts des parties, notamment lorsque le tribunal arbitral n’est pas encore saisi. Dès lors, prenant en considération les particularités de l’arbitrage et plus particulièrement du déroulement du procès arbitral, l’intervention du juge est indispensable pour résoudre temporairement une urgence sur le fondement de l’apparence d’un droit afin de conférer une force exécutoire aux décisions de l’arbitre. Le tribunal arbitral n’est pas seul à décerner ces mesures. Il est subséquemment légitime de se questionner sur la position du juge au sujet des mesures provisoires et conservatoires lors d’un arbitrage. Après analyse des diverses dispositions du Code de l’arbitrage, il résulte que le législateur met un point d’honneur à orchestrer la relation entre l’arbitre et le juge étatique. Pour ce faire, il opte pour une distribution de compétences entre le juge du provisoire et l’arbitre, une sorte de répartition qui implique un retrait de la compétence exclusive de l’arbitre en termes de mesures provisoires et conservatoires. Aussi, délibérément choisi par les parties, l’arbitre prononce le droit, mais sa décision est dénuée d’imperium. C’est la raison pour laquelle le recours au juge étatique est indispensable afin de soutenir sa décision. En matière de mesures provisoires et conservatoires, la compétence du juge judiciaire est à la fois partagée avec l’arbitre, mais aussi exclusive.

Dissenting Opinions in International Commercial Arbitrations - Mohanty, Gautam (Central European University, 2017)
A dissenting opinion with reference to International Commercial Arbitrations elementarily denotes the expression of disagreement by an Arbitrator in relation to both the reasoning and the result of the award granted by the majority of the Tribunal. Though still at a nascent stage, the practice of delivering dissenting opinions is one which needs to be duly noted and taken into due consideration because of the incidental and collateral questions that it nurtures. Fundamentally, a dissenting opinion raises concerns related to the effect, the nature and the rectitude of such opinions. One such collateral question is the enforceability of such dissenting opinions and the repercussions that follow in the context of an arbitral award delivered by the majority. In addition to the above raised question, through this thesis the author will also address other questions such as whether the act of delivering a dissenting opinion is an indicator of the increased sense of maturity of arbitrators in international commercial arbitration? Whether the dissenting opinion possesses any precedential value to the arbitration cases arriving prospectively? and How do such opinions contribute to the development of arbitration jurisprudence. Moreover, through this thesis the author will also attempt from a comparative perspective to examine and make an incisive analysis of the governing rules of arbitration across various arbitration regimes such as ICSID, LCIA which already have a wellestablished arbitration jurisprudence.

Alternative Dispute Resolution in Oil and Gas Contracts Law: An Analysis - Kareem, Kareem Kawa (Near East University, 2017)
The industry of oil and gas is not peculiar to question anymore, inferable from the global condition as well as its various dimensions. While trying to complete an agreement procedure, it would barely be clear to expect the thing that could happen in the emergence of a debate. Hazard moving and fragmented contracting lie at the heart of the organization relationship innate in the obtainment and financing of extensive scale undertakings, such as power plants, oil and gas pipelines, and condensed natural gas facilities. An examination of gas bonds gives exact proof of the hazard moving results of legally binding inadequacy. This thesis is a basic examination of the discipline we call the law of oil and gas. A number of the imperfections connected with this "specific" status. Jurisprudential with its "uncommon" status. Jurisprudential imperfections have created as courts leave from essential contract, property, or tort law in quest for natural resources ideas. The marvel isn’t restricted to natural resources law but instead can occur in any "law of" setting. This article delineates the issues connected with oil and gas law by dissecting legal ways to deal with perceiving and applying "inferred agreements" under the oil and gas rent. By contrasting the experience and results under the oil and gas lead to the result under an agreement law investigation, it is conceivable to assess whether a specific "oil and gas" govern is vital or prudent. In the past quarter-century, huge changes have happened in the ways legal advisors approach strife. There have been uncommon endeavors to create systems went for more proficient, not so much expensive, but rather more fulfilling determination of contention, including more broad and suitable utilization of intercession and other " alternative dispute resolution " (ADR) approaches. This review analyzes what is known and not considered about the development and effect of ADR in government and state courts, in the business division, and in work and shopper settings. The investigation inspects the relationship amongst ADR and court trial, additionally underlines the more extensive employments of and method of reasoning for intercession and different process decisions. This study concentrates on the oil and gas contract with question by ADR.

State interference through domestic courts in international commercial arbitration - Badenhorst, Casper Hendrik Jacobus (University of Johannesburg, 2016)
Keywords: Arbitrage; Arbitragem; Arbitration; International and municipal law; International commercial arbitration

La prérogative de l'arbitre de relever un moyen d'office - Gaucher, Natalia (Aix-Marseille Université, 2016)

دور المحكم في الخصومة التحكيمية - حمودي, سمية (جامعة الوادي university el-oued, 2016)
تناولت هذه الدراسة أهم عنصر من عناصر عملية التحكيم، ألا وهو دور المحكم في خصومة التحكيم، وذلك من خلال معرفة شروط وإجراءات اختاره ومركزه القانوني وسلطاته والتزاماته . و قد بدأت الدراسة بمقدمة تضمنت العناصر الرئيسية للبحث وتناولنا ف الفصل الأول التعريف بالمحكم من خلال بيان معناه وتميزه عن القاضي والخبير والمصالح والوكيل، كذلك بيان الشروط الواجب توافرها في المحكم، كما تم توضيح المركز القانوني للمحكم في خصومة التحكم وكذا بيان طرق تشكيل هيئة التحكيم. كما تناولنا سلطات المحكم، سواء كانت ناشئة عن اتفاق التحكيم، أم المخولة له بموجب القانون، وبيان الالتزامات المرمية على عاتقه أثناء مباشرته لمهمته، وكل ذلك من خلال الفصل الثاني. ومن أهم النتائج التي خلصت إليها الدراسة، هي أن المحكم يتمتع بسلطات واسعة في خصومة التحكيم، إلا أن هذه السلطات الواسعة ليست مطلقة بلا قيود، وإنما يفرض على المحكم عدة التزامات منذ قبوله مهمة التحكيم وحتى صدور الحكم الفاصل في النزاع مرورا بالتزاماته أثناء سير الاجراءات مع مراعاة احترام المبادئ الأساسية للتقاضي. Cette étude portait sur l'élément le plus important du processus d'arbitrage, à savoir le rôle d'arbitre dans l'arbitrage des différends, et grâce à la connaissance des conditions et des procédures choisies statut juridique, pouvoirs et obligations. L'étude a commencé par une introduction comprenait les principaux éléments de la recherche et nous traitée dans le premier arbitre de définition de chapitre à travers les moyens de déclaration et de le distinguer du juge et expert, des intérêts et de l'agent, ainsi que la déclaration des conditions à remplir par l'arbitre, a également clarifier le statut juridique d'un arbitre dans le contrôle des différends, ainsi qu'une description des moyens de la formation du tribunal. Comme nous approchions les autorités de l'arbitre, que ce soit en raison de la convention d'arbitrage, ou qui lui sont conférés en vertu de la loi, et la déclaration des obligations jetées sur lui-même pendant l'exécution de leur mission, et tout au long du deuxième trimestre. Parmi les résultats les plus importants de l'étude, il est que l'arbitre dispose de larges pouvoirs à l'arbitrage des différends, mais ces larges pouvoirs est pas absolue, sans restrictions, mais a imposé à l'arbitre plusieurs engagements depuis accepter la tâche d'arbitrage et jusqu'à la délivrance de l'arbitre décisif dans le conflit par ses obligations au cours de la procédure, avec en tenant compte du respect des principes de base du litige
Keywords: Arbitrage des différends; Arbitration; Arbitre; Obligations de l'arbitre; Pouvoirs de l'arbitre; Statut juridique; Tribunal arbitral; التزامات المحكم; الخصومة التحكيمية; المحكم; المركز القانوني; سلطات و; هيئة التحكيم

Alle origini della mediazione - Donati, Viola (Università di Pisa, 2014)
L’esigenza di alleggerire il carico dei tribunali mediante forme di soluzione diverse e alternative al processo giurisdizionale trae le sue origini da esperienze culturali remote: l’arte della composizione del conflitto rappresenta un'attività di cui l’uomo si è fin da subito dovuto occupare, per lo meno dal momento in cui ha cominciato a vivere all’interno di una comunità, proprio perché si tratta di un’attività che sfiora tutti gli aspetti della vita sociale. La mediazione ha origini antichissime, infatti la necessità di sviluppare nei secoli procedure alle quali ricorrere per garantire un'ordinata convivenza e armonia sociale risale già all'antica Roma del V secolo A.C.: la prima delle XII Tavole (il più antico diritto scritto dell’antichità romana), richiama il tentativo di compromesso da esperirsi davanti al pretore con cui le parti in lite trovano un accordo sull’oggetto del contendere, nel qual caso il giudice è tenuto a consacrarlo con l’emanazione della sentenza mentre in caso di mancato raggiungimento di un accordo allora si sarebbero adite le vie giudiziali instaurando il processo. Le origini della mediazione trovano fondamento in tempi antichi anche in Paesi dell’estremo oriente ed in particolare in Cina dove la mediazione fu lo strumento principale nella risoluzione delle dispute: Confucio sosteneva che il modo migliore per dirimere una disputa fosse la persuasione morale e il raggiungimento di un accordo, piuttosto che la coercizione del Sovrano. L’idea stessa di “compromesso” è profondamente radicata nella cultura cinese, infatti non tener in alcun conto gli interessi dell’altra parte è considerato particolarmente deplorevole sul piano etico-giuridico ed il pensiero confuciano è promotore della mediazione, tanto che l’istituto continua tuttora ad essere praticato nella Repubblica Popolare Cinese. In tempi più recenti, dopo l’unificazione del Regno d’Italia e la conseguente stesura del codice di procedura civile del 1865, il legislatore ha dedicato ampio spazio alla composizione bonaria delle controversie, disciplinando la conciliazione nel titolo preliminare all'art.1, dando vita così alla figura professionale del giudice conciliatore: caratteristiche essenziali del procedimento consistevano nella compresenza della funzione conciliativa con quella giurisdizionale nel giudice conciliatore, la municipalità del giudice stesso e infine la completa assenza di formalità (il rito si svolgeva verbalmente) per consentire a tutti un facile accesso alla procedura. Se invece apriamo il Codice di procedura vigente, per trovare un accenno alla conciliazione bisogna aspettare l'art. 320, e questa sfiducia a cui è andata in contro la figura del giudice conciliatore è arrivata fino ai nostri giorni. Negli USA la mediazione fu introdotta come sistema volontario (nelle controversie sindacali tra le compagnie ferroviarie e i loro dipendenti) nel 1887, con la legge sul commercio tra gli Stati (Intestate Commerce Act), e a partire dalla fine degli anni ’60 trovò un applicazione sempre maggiore. Ma la svolta fondamentale si ebbe nel 1998, in occasione della modifica del Titolo 28° della Carta dei Diritti e nell'Alternative Dispute Resolution Act, che consacrarono il successo della cultura alternativa della gestione del conflitto nella società americana. Oggi il ricorso agli A.D.R. ha portato ad una riduzione del contenzioso giudiziario di quasi il 90%. Visto l’esito positivo avutosi oltreoceano, nell’aprile del 2002 la Commissione Europea ha presentato un Libro Verde relativo ai modi alternativi di risoluzione delle controversie in materia civile e commerciale per promuovere l’utilizzo della mediazione, ed in seguito alla Direttiva n. 2008/52/CE il governo italiano ha emanato il D.lgs. 28/2010 al fine di coordinare le disposizioni vigenti in materia di mediazione e conciliazione in ambito civile e commerciale, solo che appena due anni dopo, il 6 dicembre 2012, la Corte costituzionale ha dichiarato l'illegittimità del decreto per eccesso di delega legislativa, così che il governo Letta ha cercato di disciplinare nuovamente l'istituto con la Legge n.98/2013, sebbene stavolta la mediazione sia stata prevista come temporanea perché contemplata come obbligatoria per i soli quattro anni successivi alla sua entrata in vigore, a metà dei quali il ministero di giustizia avvierà un monitoraggio per valutare se la sperimentazione della procedura di mediazione ha funzionato. Speriamo che intanto la “cultura della mediazione” cominci a diffondersi anche in Italia.
Keywords: ADR; Conciliation; Conciliazione; MARC; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

L'arbitrage maritime : une étude comparative entre Londres et Paris - Khaldi, Jihane (Aix-Marseille Université, 2014)
Keywords: Arbitrage; Arbitration

Mediación mercantil. Mediación mercantil empresarial - Rojas Roldán, María de la Encarnación (Universidad Internacional de Andalucía, 2014)
Trabajo de Curso de Experto Universitario en Mediación Civil, Familiar, Mercantil y Organizaciones Complejas (2013). Tutora: María Sonia González Ortega. El objetivo del presente trabajo es abordar la Mediación en el seno de las organizaciones, teniendo en cuenta que estas constituyen sistemas de interrelación entre personas, donde confluyen numerosos intereses. Se trata por tanto, de abordar la resolución de los problemas no solo existentes sino de los emergentes, aportando herramientas eficaces en el desarrollo de la actividad empresarial, que permitan gestionar y modular los conflictos, de forma que los mismos, se transformen en oportunidades de mejora y de crecimiento empresarial.
Keywords: Mediación; Mediation; Médiation

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

La priorité chronologique reconnue à l'arbitre en droit maritime français, particularisme ou universalisme ? Le principe dit de compétence-compétence - Yildiz, Irfan (Aix-Marseille Université, 2012)
L’abandon progressif du contrôle de l’opposabilité de la clause d’arbitrage au destinataire par la juridiction étatique au profit de l’arbitre sur le fondement de l’aspect négatif du principe de compétence-compétence a donné lieu à de nombreux critiques. Certains auteurs l’ont approuvé, valorisant une application rigide de l’effet négatif du principe, tandis que d’autres l’ont critiqué solidement. Ainsi, il est légitimement permis de s’interroger sur les excès de l’effet négatif du principe de compétence-compétence et le bien-fondé de l’abandon du contrôle de l’opposabilité à l’arbitre par les juges étatiques. Pour ce faire, nous allons, dans un premier temps, examiner le droit accordé à l’arbitre d’être juge de sa propre compétence de manière prioritaire, plus précisément le principe de compétence-compétence (Chapitre I). Ensuite, nous allons nous interroger sur l’extension de la clause d’arbitrage au destinataire au regard du principe de compétence-compétence, qui est considéré de remettre en cause ce principe (Chapitre II).
Keywords: Arbitre droit maritime; Compétence-compétence; Transport maritime

L'annulation de la sentence arbitrale au Québec et dans l'espace OHADA : une approche comparée. - Kouassi, Fabrice Constant (Université de Sherbrooke, 2011)
Le processus de règlement des litiges par la voie de l’arbitrage a nourri des ambitions économiques énormes dans les sphères juridiques où ce mécanisme a été instauré. L’efficacité de ce processus qui signifie entre autre un processus ayant abouti à une application, voire une exécution effective des protagonistes est un gage de la réalisation de ces ambitions. Or, ce processus peut être compromis du fait de l’annulation de la sentence arbitrale par un juge dont l’intervention dans le processus peut soit le renforcer, soit l’annihiler fondamentalement. Cette situation explique dans une large mesure les raisons pour lesquelles la doctrine juridique se place en faveur d’une collaboration solide entre la justice publique et la justice privée de l’arbitrage. Comment cette question de l’annulation de la sentence arbitrale est abordée dans les sphères juridiques du Québec et de l’Ohada? Quels sont les effets juridiques issus de la comparaison de cette situation dans chacune de ces sphères? Telle se présente la substance de cette recherche dont la méthode comparative est alimentée par le paradigme de l’herméneutique juridique et son corollaire le pluralisme juridique. Les résultats issus du dialogue comparatif devraient participer à une amélioration des situations problématiques décelées dans les sphères concernées. The rule process of lawsuits based on arbitration has filled out huge economic ambitions related to judicial spheres where this mechanism has been established. The efficiency of this process, which among others, has led to an application, indeed a real execution of the protagonists, is somewhat a guarantee to the fulfilment of these ambitions. However, this process can be compromised because of the cancellation of the arbitral sentence by a judge whose intervention in the process can either reinforce it or destroy it. This situation mainly explains the reasons why the juridical doctrine is in favour of a solid collaboration. How do the juridical sphere of Quebec and Ohada tackle this issue of the cancellation of the arbitral sentence? What are the juridical effects stemmed from the comparism of this situation in both spheres? The way the substance of this research appears and whose comparative method is fed by the paradigm of the juridical hermeneutics and its juridical pluralism corollary. The results stemmed from the comparative dialog should participate in improving problematic situations detected in the applied spheres.
Keywords: Annulation; Arbitrage; Arbitragem; Arbitration; Litiges; Sentence arbitrale

L'arbitre international : étude de droit comparé - Partida, Sebastián (Université Paris 2, 2011)

La problématique du consentement à l'arbitrage multipartite au sein des groupements de sociétés - Manirabona, Amissi Melchiade (Université de Montréal, 2006)
L'arbitrage étant une institution basée sur la volonté des parties, le consentement à la procédure arbitrale multipartite soulève de nombreuses questions relativement à la manière dont les parties expriment leur intention de faire partie d'une instance unique. Cette étude vise à déterminer les conditions dans lesquelles l'arbitre peut arriver à unifier la résolution des litiges qui impliquent les groupements de sociétés. Le plus naturel des moyens pour aboutir à une procédure multipartite est de prévoir cette possibilité à travers la convention d'arbitrage. Cela peut notamment provenir de la signature d'une convention d'arbitrage unique par toutes les parties concernées. Dans certains cas précis, l'arbitrage multipartite peut également résulter de plusieurs conventions d'arbitrage spécialement lorsque les parties participent à la réalisation d'un même ouvrage. Cependant, il arrive souvent qu'une partie qui n'a pas signé la convention d'arbitrage soit obligée à participer à l'instance. Même sans y être obligée, une partie non-signataire de la convention d'arbitrage peut aussi demander de participer à l'arbitrage pour défendre ses intérêts. Pour pouvoir admettre la participation à la procédure d'un tiers non-signataire de la convention d'arbitrage, les arbitres ont recours à plusieurs notions prévues par les droits internes. C'est ainsi que la levée du voile corporatif, la théorie de la réalité économique et le principe de l'estoppel constituent les meilleurs outils pour les arbitres d'amener à la procédure, par force ou sur demande, un non-signataire de la convention d'arbitrage. Enfin, les mécanismes du Code civil servent efficacement à neutraliser les effets du principe de relativité de la convention d'arbitrage. Il s'agit notamment de la bonne foi, du mandat, de la stipulation pour autrui et de la cession. Arbitration as an institution based on the intention of the parties, the consent on the multi-party arbitration procedure raises many problems relating to the way in which the parties express their intention to participate in a unique arbitration forum. This study aims to determinate the manner in which the arbitrator can join disputes resolution involving the groups of companies. The normal way to get a multi-party procedure is to provide it in an arbitration clause. This can be by signing a single arbitration agreement by all the parties involved. In certain cases, the multi-party arbitration can also be possible with several arbitration agreements especially when the parties took part in carrying out ofthe same economic operation. However, in other situations, the multi-party arbitration procedure is unrelated to consent. A non-signatory party can nevertheless be bound by an arbitration agreement signed by an other party. To allow the participation in the arbitration procedure of a third party non-signatory of the arbitration agreement, the arbitrators use several concepts provided chiefly by the national laws. 80, the lifting of the corporate veil, the doctrine of economic reality and estoppel, are the best tools for the arbitrators to bring to the arbitration procedure, by force or on request, a non-signatory of the arbitration agreement. Lastly, the mechanisms of the Civil code are used with efficiency by arbitrators to neutralize the effects of the relativity principle of the arbitration agreement. Those mechanisms are in particular the good faith, mandate, stipulation for another and assignment.
Keywords: Arbitrage; Arbitragem; Arbitration; Convention d'arbitrage; Effets (extension); Extension of the arbitration clause; Groupes de sociétés; Groups of Companies; Third Party non-signatory; Tierces parties non-signataires